2016
DOI: 10.1007/s00464-016-5024-5
|View full text |Cite
|
Sign up to set email alerts
|

Prospective randomized controlled trial comparing standard analgesia with combined intra-operative cystic plate and port-site local anesthesia for post-operative pain management in elective laparoscopic cholecystectomy

Abstract: This PRCT shows significantly improved pain control with somatovisceral pain blockade over non-opioid/opioid analgesic combinations following LC for symptomatic cholelithiasis. For centers not utilizing adjunctive local anesthetic for LC, this topical use of bupivacaine may improve patient comfort during recovery. This trial was registered on www.ClinicalTrials.gov NCT# 01972620.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 65 publications
0
11
0
Order By: Relevance
“…Pain after a laparoscopic cholecystectomy (LC) is related to abdominal distention, port-site incision, and phrenic nerve irritation due to CO 2 insufflation; therefore, pain felt after removal of the gallbladder has both visceral and somatic origins (3) . Acute postoperative pain is correlated with increased myocardial ischemia, thromboembolic and pulmonary complications, changes in the immune system due to opioid use, an increased hospital stay, an inadequate quality of life, and chronic pain at a rate of 3-56 percent (4,5) .…”
Section: Introductionmentioning
confidence: 99%
“…Pain after a laparoscopic cholecystectomy (LC) is related to abdominal distention, port-site incision, and phrenic nerve irritation due to CO 2 insufflation; therefore, pain felt after removal of the gallbladder has both visceral and somatic origins (3) . Acute postoperative pain is correlated with increased myocardial ischemia, thromboembolic and pulmonary complications, changes in the immune system due to opioid use, an increased hospital stay, an inadequate quality of life, and chronic pain at a rate of 3-56 percent (4,5) .…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have reported that spinal anesthesia and local peritoneal anesthesia have a lower rate of postoperative complications compared with general anesthesia. 26 - 28 …”
Section: Discussionmentioning
confidence: 99%
“…The effect of intraperitoneal LA was examined in 12 studies, [81][82][83][84][85][86][87][88][89][90][91][92] which demonstrated no change in LOS (p = 0.200) or day case rates (p = 0.110). A total of five studies 81,[93][94][95][96] were found examining the effect of combined intraperitoneal and incisional LA and this likewise did not show a significant reduction (p = 0.060). Three studies [97][98][99] examined the effect of intraoperative transversus abdominis plane (TAP) blocks versus no TAP blocks and systematic review found no difference in LOS or day case rate.…”
Section: Local/regional Anaesthesiamentioning
confidence: 96%